ABAH GURU SEKUMPUL : Kajian Sosial Agama terhadap Pemasangan Potret Ulama di Unit Usaha Masyarakat Kota Banjarmasin - Enta Malasinta Lantigimo; Ripaldi; Lia Afriliani (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2023)
Displaying of pictures of ulama on the walls of business units, in particular the picture of Abah Guru Sekumpul, is a tradition of Muslims in Banjarmasin, the main purpose of which is to relate to Islamic spirituality, including for blessings in business as well as respect for Servants of Allah. Interestingly, even though the perpetrators of displaying the images are Muslims, their positive impact is felt in the social life in general society. Based on the research results, data was found that traders from various backgrounds and various religious backgrounds would really enjoy honest and mutually beneficial business transactions based on the belief that displaying pictures of ulama is a symbol of goodness in doing business. This situation will greatly affect social relations, because it will foster a sense of mutual need and mutual trust which will lead to a peaceful, harmonious and comfortable relationship in people's lives.